2003
DOI: 10.1554/02-393
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Viability Selection Among Cohorts of Juvenile Red Squirrels (Tamiasciurus Hudsonicus)

Abstract: Selection will result in observable changes in traits only if it acts consistently in space and time, but few estimates of selection in natural populations have been temporally replicated. Here we estimate viability selection on nestling growth rates for 13 cohorts (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001) of red squirrels (Tamiasciurus hudsonicus) from a natural population located in southwestern Yukon, Canada. Directional selection on nestling growth rates varied in magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(110 citation statements)
references
References 33 publications
1
108
1
Order By: Relevance
“…Th e mechanism by which female red squirrels assess their relatedness to juveniles or their dams is unknown and is a current focus of research at our study site. Although not specifi cally designed to study kin discrimination, previous cross-fostering experiments found that genetic and foster off spring grew at the same rate 9,19 , suggesting that female red squirrels do not diff erentially invest in Cases A1 -A5 were adopted, whereas cases NA1 and NA2 were not adopted even though there were lactating kin ( r ≥ 0.125) nearby. The number of lactating females nearby was estimated relative to the orphaned juvenile and not the surrogate dam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e mechanism by which female red squirrels assess their relatedness to juveniles or their dams is unknown and is a current focus of research at our study site. Although not specifi cally designed to study kin discrimination, previous cross-fostering experiments found that genetic and foster off spring grew at the same rate 9,19 , suggesting that female red squirrels do not diff erentially invest in Cases A1 -A5 were adopted, whereas cases NA1 and NA2 were not adopted even though there were lactating kin ( r ≥ 0.125) nearby. The number of lactating females nearby was estimated relative to the orphaned juvenile and not the surrogate dam.…”
Section: Discussionmentioning
confidence: 99%
“…Using these natal relationships, we constructed a complete maternal pedigree spanning multiple generations. 19 and R é ale et al 21 ). Parturition date and juvenile growth rate were standardized within grid -year combinations, and the intercept of the model was forced through zero to correspond to the biologically relevant model in which females who did not produce any juveniles had zero ARS.…”
Section: Methodsmentioning
confidence: 95%
“…Arnqvist and Johansson, 1998). Rearing damselfly larvae collected from a fishless site with versus without dragonfly predator cues could evaluate the degree to which breaking forces, cuticle width and joint size may express adaptive plastic responses to local predation risk, while longitudinal (cohort) methods in the wild could address selection (McAdam and Boutin, 2003).…”
Section: Research Articlementioning
confidence: 99%
“…We found no effect of maternal age or litter size, but parturition date was associated with offspring LRS. Parturition date is a heritable maternal trait in red squirrels [54] that has been found to affect offspring recruitment [55]. Parturition date, therefore, represents a MGE on offspring fitness.…”
Section: Discussionmentioning
confidence: 99%